Kin17 knockdown suppresses the migration and invasion of cervical cancer cells through NF-κB-Snail pathway - Zhong, Meifeng (Int J Clin Exp Pathol, 2020)
Cervical cancer is one of the most common cancers in women worldwide. Metastasis in cancer has been a Gordian knot due to unsatisfactory clinical treatments. KIN17, a highly conserved gene from yeast to human, up-regulation is associated with the pathogenesis and development of several common cancers. Our previous works revealed that elevated expression of kin17 observed in cervical cancer tissues showed a close association with lymph node metastasis. This study aimed to explore roles and mechanisms of kin17 in the migration and invasion of cervical cancer cells. Cervical cancer cell lines HeLa and SiHa with kin17 knockdown were constructed by using recombinant lentiviral vector that carry specific siRNA targeting KIN17 gene. The mRNA and protein levels of kin17 in cells were determined by RT-qPCR and western blotting, respectively. Wound healing assay and transwell assays were performed to assess the migration and invasion abilities of the cancer cells, respectively. The expression of signaling proteins involved in the NF-κB-Snail pathway was analyzed by western blotting. As our results showed, the mRNA and protein levels of kin17 in HeLa cells and SiHa cells showed a significant decrease by transfection with recombinant lentiviral vector carrying specific siRNA. Compared with control group, the migration rates were decreased in the kin17 knockdown group in both HeLa and SiHa cell lines in wound healing assay as well as transwell assay without matrigel. Kin17 knockdown also reduced the cell invasion number of both HeLa and SiHa cells. In addition, the phosphorylation of nuclear factor Kαppa B (NF-κB) p65, IKαppa B kinase α (IKKα), and IKαppa B α (IκBα) in NF-κB pathway and the expression of Snail were decreased in HeLa cells and SiHa cells by kin17 knockdown. Our results demonstrated that knockdown of kin17 in cervical cancer cells suppressed cell migration and invasion, and inhibited the activity of NF-κB signaling pathway and the expression of Snail. These findings suggested kin17 as an essential regulator of the cell migration and invasion and the underlying molecular mechanism involved NF-κB-Snail pathway in cervical cancer. This might serve as a novel molecular therapeutic target for treating cervical cancer metastasis.